Modulation of cognition and anxiety-like behavior by bone remodeling - Lori Khrimian; Arnaud Obri; Gerard Karsenty (Elsevier, 2017)
Objective: That the bone-derived hormone osteocalcin is necessary to promote normal brain development and function, along with its recently described sufficiency in reversing cognitive manifestations of aging, raises novel questions. One of these is to assess whether bone health, which deteriorates rapidly with aging, is a significant determinant of cognition and anxiety-like behavior. Methods: To begin addressing this question, we used mice haploinsufficient for Runx2, the master gene of osteoblast differentiation and the main regulator of Osteocalcin expression. Control and Runx2+/− mice were evaluated for the expression of osteocalcin's target genes in the brain and for behavioral parameters, using two assays each for cognition and anxiety-like behavior. Results: We found that adult Runx2+/− mice had defects in bone resorption, reduced circulating levels of bioactive osteocalcin, and reduced expression of osteocalcin's target genes in the brain. Consequently, they had significant impairment in cognitive function and increased anxiety-like behavior. Conclusions: These results indicate that bone remodeling is a determinant of brain function. Keywords: Runx2, Osteocalcin, Bone remodeling, Cognition